(untitled) (American Journal of Aquaculture and Animal Science, 2025)
A cross-sectional study was conducted from June 2021 to November 2021 with the objectives to estimate the prevalence bovine babesiosis and identify the associated potential risk factors and tick species involved in the transmission of this disease in Galka-Ayo district, Somalia. A random sampling technique was employed for selecting the sampling units and the logistic regression analysis was used to determine the association of hypothesized risk factors with positivity for bovine babesiosis. A total of 348 blood samples were collected and examined for the presence of bovine babesiosis by Giemsa staining technique. An overall 11.2% (43/384 babesiosis prevalence was estimated. Except for age and sex, body condition, village and tick infestation showed statistically significant associations (P<0.05) with the occurrence of the disease. The highest prevalence of bovine babesiosis was recorded in Roox (16.94%) and lowest in Agaran (2.70%) villages. However, there was a statistically significant variation in positivity of bovine babesiosis between different localities (P=0.001). According to multivariate logistic regression analysis, the odd of bovine babesiosis occurrence in medium and poor body condition animals were 3.19 and 2.73 times more likely than in good body condition animals, respectively. This difference was found to be statistically significant (P=0.015). A higher prevalence of babesiosis was found in tick-infested (13.91%) than in non-infested cattle (5.08%) and this difference was statistically significant (P=0.001). The mean ± Standard deviation packed cell volume (PCV) was 23.56 ± 4.465 for the overall study animals, 20.56 ± 3.896 for the infected and 24.47 ± 4.429 for the non-infected cattle. There was statistically significant difference in mean PCV value between infected and non-infected cattle (P=0.02). In conclusion, implementing surveillance systems, raising cattle owners’ awareness on tick-borne diseases, further future studies using more refined serological and genetic techniques, maintaining enzootic stability, and enhancing pre-munity by improving cares given to calves is essential.